Breeding systems of shrubs and trees of a Brazilian savanna - Saraiva, L. C.; Cesar, O.; Monteiro, R. (Inst Tecnologia Parana, 1996)
The reproductive biology of shrubs and trees of a preserved savanna (''cerrado'') area in the municipality of Corumbatai São Paulo State, Brazil was studied. The floral sexuality of 135 species were characterized, with 85.2 % hermaphroditic, 9.4 % dioecious, 4.5 % monoecious, and one determine the breeding systems. Nine apomictic species were found, all belonging Melastomataceae. Among the twelve sexual reproducing species, seven (58.3 %) proved to be self-compatible, and five (41.7 %) self-incompatible. Anemophily was found in five species, although pollinations systems were not investigated in other species.
Keywords: anemophily; apomixis; breeding systems; cerrado; density; dioecy; dispersion; self-incompatibility